Menakar Kembali Nilai Keperempuanan: Analisis Pascastrukturalisme atas Tiga Karya - Prasetyo, Teguh (Jurnal Seni Urban dan Industri Budaya, 2023)
In the construction of patriarchal culture, women and the values that accompany them are often placed in a position that is destined to be supporting and below the position of men. Literary works were born as a response to the cultural conditions that accompanied them. On the one hand, it can be a mirror, but on the other hand, it can also be a stimulus for critical thinking about the culture itself. Literary works such as Pengakuan Pariyem by Linus Suryadi A.G., "Baju" by Ratna Indraswari Ibrahim, and "Air Suci Sita" by Leila S. Chudori emerged to stimulate critical thinking about the value of womanhood which has been constructed by patriarchal culture. Therefore, this article will try to dissect the forms of critical thinking regarding patriarchal culture and feminine values that exist in these three literary works. The method used in this article is a qualitative method with the theory of post-structuralism theory, especially Derrida's deconstruction. The results of this research show that the values of the three literary works express a critics against the construction of womanhood as subject to patriarchal culture.Dalam konstruksi budaya patriarki, perempuan dan nilai-nilai yang menyertainya seringkali ditempatkan pada posisi yang ditakdirkan menjadi pendukung dan di bawah posisi laki-laki. Karya sastra kemudian lahir sebagai respons terhadap keadaan budaya yang menyertainya. Di satu sisi bisa saja menjadi cermin, tetapi di sisi lain juga sebagai rangsangan berpikir kritis terhadap budaya itu sendiri. Karya-karya seperti Pengakuan Pariyem karya Linus Suryadi A.G., cerpen “Baju” karya Ratna Indraswari Ibrahim, dan cerpen “Air Suci Sita” karya Leila S. Chudori hadir untuk merangsang pemikiran kritis terhadap nilai keperempuanan yang selama ini dikonstruksi budaya patriarki. Oleh karena itu, artikel ini akan mencoba membedah bentuk pemikiran kritis terhadap budaya patriarki dan nilai keperempuanan yang ada dalam ketiga karya tersebut. Metode yang digunakan dalam artikel ini adalah metode kualitatif dengan pisau bedah teori pasca-strukturalisme, terutama dekonstruksi Derrida. Hasil dari penelitian ini menunjukkan bahwa nilai ketiga karya di atas menyatakan gugatan terhadap konstruksi keperempuanan yang tunduk pada budaya patriarki.  TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in Indonesian Translate to English    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Indonesian to EnglishPRO Never translate Indonesian Never translate jurbalurban.pascasarjanaikj.ac.id